Variasi lama waktu fermentasi terhadap karakteristik kimia teh kombucha: meta-analisis - Rina Dias Agustin; Puspo Edi Giriwono; Endang Prangdimurti (AGROINTEK, 2024)
One type of beverage that has functional effects and has been known for a long time is kombucha tea, a fermented drink made with tea leaves, sugar, and Symbiotic Culture of Bacteria and Yeast (SCOBY). Kombucha tea tastes sourly like apple vinegar, sparkling contains polyphenol compounds, organic acids, other biomolecules, and probiotics. The fermentation time is a factor that needs to be considered in making kombucha tea. Much research has been done on kombucha tea, but the variation in duration of the fermentation process is very diserve, so a meta-analysis is needed to obtain valid and informative conclusions from a comprehensive study about the effect of fermentation time on the kombucha tea chemical characteristics. The PRISMA flowchart and the effect size of Standardized Mean Difference (SMD) in the form of Hedges'd were choosen as  a quantitative synthesis method of meta-analysis. The results showed that the fermentation process conducted for 8-14 days had a strong effect on all parameters (flavonoid, ethanol, acetic acid levels, total phenolic, total acidity, and antioxidant activity) with SMD values 0.8, p values 0.001 to 0.732, and heterogeneity values of 57,62% to 89,40%. Kombucha tea, with a fermentation time of 7 days had significantly higher antioxidant activity. The length of the fermentation process has the strongest effect on the acetic acid levels of kombucha tea.